2002
DOI: 10.1113/jphysiol.2001.015446
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of haem oxygenase activity increases leukocyte accumulation in the liver following limb ischaemia‐reperfusion in mice

Abstract: Although the consequences of trauma or infection are normally controlled at the site of injury, loss of local control may lead to a whole body response, which has been identified clinically as the systemic inflammatory response syndrome (SIRS). If this systemic inflammatory process involves whole body infection, the condition is termed sepsis. In its worst case, SIRS results in multiple organ dysfunction occurring in approximately 30 % of septic patients, in 24 % of patients suffering from pancreatitis, in ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
44
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 32 publications
4
44
0
1
Order By: Relevance
“…Our data are congruent with existing findings regarding the actions of this enzyme during I-R. It has been reported that HO-1 activity within the liver decreases leukocyte interaction with the endothelium (38), possibly by suppressing the induction of adhesion molecules (36). HO-1 has also been reported to suppress inflammatory cytokine pathways involved in hepatic I-R injury (34).…”
Section: Discussionsupporting
confidence: 82%
“…Our data are congruent with existing findings regarding the actions of this enzyme during I-R. It has been reported that HO-1 activity within the liver decreases leukocyte interaction with the endothelium (38), possibly by suppressing the induction of adhesion molecules (36). HO-1 has also been reported to suppress inflammatory cytokine pathways involved in hepatic I-R injury (34).…”
Section: Discussionsupporting
confidence: 82%
“…Bilateral hindlimb I/R has been extensively used in our laboratory as a model of SIRS, which closely resembles the acute traumatic and ischemic insult seen in SIRS patients (Wunder et al, 2002). It has been demonstrated that hindlimb I/R causes cellular injury in remote organs (e.g., liver, lung, and intestine) and contributes to the development of MODS (Wunder et al, 2002;Yassin et al, 2002).…”
mentioning
confidence: 99%
“…It has been demonstrated that hindlimb I/R causes cellular injury in remote organs (e.g., liver, lung, and intestine) and contributes to the development of MODS (Wunder et al, 2002;Yassin et al, 2002).…”
mentioning
confidence: 99%
“…5). Eigene Untersuchungen an einem SIRS-Tiermodel (Ischämie/Reperfusion der Hinterläufe) zeigten, dass die Induktion der Hämoxygenase nicht nur das Ausmaß der Leberzellschädigung und Störung der Mikrozirkulation in den Sinusoiden reduziert, sondern auch die Adhäsion von Leukozyten in der Mikrozirkulation der Leber vermindert [65]. Das Zusammenspiel von CO und NO in der Steuerung der Mikrozirkulation der Leber ist komplex und weiterhin Gegenstand der aktuellen Forschung.…”
Section: Kohlenmonoxidunclassified